ΜΗ ΓΡΑΜΜΙΚΗ ΚΙΝΗΜΑΤΙΚΗ ΑΛΛΗΛΕΠΙΔΡΑΣΗ ΕΔΑΦΟΥΣ ΠΑΣΣΑΛΟΥ - Μισιρλής, Παναγιώτης (Σχολή Πολιτικών Μηχανικών, 2018)
Design of piles against kinematic loading is rarely applied in engineering practice. According to seismic codes, kinematic soil–pile interaction should be taken into account only when the pile is intersected by interfaces with large stiffness contrast of the consecutive soil layers. Although the last decade a considerable amount of studies has been devoted to this subject, only a few of them deal with soil nonlinearity, and, to the best of the author’s knowledge, there is still no published paper that thoroughly investigates the role of group action on soil-pile kinematic interaction under intense nonlinear soil response conditions. In this paper, the results from a thorough finite element analysis with code PLAXIS are presented in which both the piles and the soil are modeled in 3D with volume elements. A suitable plasticity model is employed for treating the nonlinear soil behaviour in cyclic loading after appropriate calibration of its parameters to match published relationships of shear modulus and damping ratio curves. The influence of key-model parameters, such as: (a) strong motion intensity, (b) stiffness contrast ratio between the soil layers, (c) depth of the interface, (d) number of harmonic cycles, (e) resonance ratio etc., on the bending moment distribution along each pile, is investigated and critically discussed. The extraction closed-form expressions for the kinematic structural forces not only in the vicinity of the interface but at the head of the pile as well, is also attempted. Additionally, accelerograms from past earthquakes are used to test the validity of the derived equations.